Internalisasi Nilai Agama dalam Edukasi Cuci Tangan pada Anak - Umi Salamah; Sa’dun Akbar (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2026)
This study examines the internalization of religious values ​​in handwashing education for children, with a focus on its implications for faith-based health education. The primary objective of this study was to improve the knowledge and skills of children at the Ngenep TPQ regarding proper handwashing, by integrating Islamic teachings on hygiene as part of worship. The method is ABCD used involved training and counseling that combined practical demonstrations, the use of visual materials, and the teaching of religious values. Key findings include a significant increase in children's handwashing knowledge and skills, as well as a deeper understanding of hygiene as part of faith. Comparative analysis with existing literature indicates that a faith-based approach to handwashing education increases children's motivation and compliance, distinguishing this study from previous studies that focused solely on medical aspects. A unique contribution of this study is the incorporation of religious values ​​into health education, which demonstrated a positive impact on fostering healthy habits. The practical implications of this study are significant, suggesting the implementation of faith-based education in health programs at religious educational institutions and opening up opportunities for further research on the integration of religious teachings with health education in other communities. Overall, this research advances the understanding of faith-based health education, providing new insights and potential applications in the field of children's health and hygiene education.